Upaya Korban Kejahatan Memperoleh Keadilan Dalam Sistem Peradilan Pidana - Agus, Azwar (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
As citizens, humans are positioned as citizens to be protected by the law; in other words, the law functions as a tool to guarantee equal rights for every citizen, without distinction. The right to education and economic rights guaranteed by the constitution for every citizen, as well as legal aid, are an effort to assist the underprivileged in the legal field. However, legal aid currently focuses more on the perpetrators than on the crime itself. Progressive law liberates the way of thinking and acting about the law, allowing the law to flow naturally to fulfil its duty to serve humanity. With that thought, humans and humanity as the centre of the times and the legal duty to realize it, thus every individual in law enforcement becomes the focal point. Constitutionally, the state is responsible for protecting human rights and providing equal standing before the law. The Code of Criminal Procedure regulates the criminal justice system. In Indonesian positive law, the regulation of the rights of crime victims is governed by several specific laws, but there is no overarching legal framework that causes crime victims to be inadequately protected. The impact of crime on victims is profound and extensive, both physically and mentally, and their recovery can take a long time. This is not balanced with the rights of the suspect or defendant, which are detailed in the Criminal Procedure Code (KUHAP); therefore, in law enforcement, not only is legal assistance provided to the suspect or defendant, but also the victim